Validation of Medicinal Chemicals Analysis Methods in Pegel Linu and Rheumatic Herbs using the TLC-UV-Visible Spectrophotometry method - Perdana Priya Haresmita; Mayla Eka Nadia; Diva Laila Ramadhani; Arief Kusuma Wardani; Dwibara Bayuaji; Anna Sa'dia Azri; Nindya Yunia Putri (Universitas Lampung Jl. Prof. Dr. Sumatri Brojonegoro No.1 Bandar Lampung, 2023)
Jamu is a traditional Indonesian medicine. Herbal medicine for rheumatism and “pegal linu” is one of the most widely consumed types of traditional medicinal products by the public, so it is a type of traditional medicinal preparation that is prone to the addition of chemical drugs (BKO). All types of traditional medicines are prohibited from containing isolated or synthetic chemicals with medicinal properties. Samples of rheumatism and “pegal linu” jamu were purchased from Grobogan, Central Java, and Gunungkidul, Yogyakarta. Two samples were purchased from Grobogan, while four samples were purchased from Gunungkidul. The standards used were mefenamic acid, phenylbutazone, and diclofenac sodium. Qualitative analysis was carried out using thin-layer chromatography and quantitative analysis using UV-visible spectrophotometry. Validation of the analytical method is carried out by setting four parameters: linearity, precision, limit of detection, and limit of quantitation. Information about the content of BKO in traditional medicines circulating in the Grobogan and Gunungkidul areas, as well as references to valid analytical methods, will greatly assist the government and academics in educating the public about the dangers of long-term consumption of traditional medicine with BKO. The results showed that three of the six samples contained BKO, and the analytical method was valid.